2020
DOI: 10.1111/acem.14016
|View full text |Cite
|
Sign up to set email alerts
|

For Us, COVID‐19 Is Personal

Abstract: W e are colleagues and friends working together in busy emergency departments (EDs) in Washington, DC. As black physicians working in urban America, we do not find the recent deluge of news reports chronicling the disproportionate effect that the coronavirus disease (COVID-19) pandemic is having on the disenfranchised and minority populations in our country shocking. We have long been witness to and are in a constant state of alarm over the legal, medical, educational, social, and economic inequities faced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Stress contributes to unhealthy behaviors 30 , 31 , in particular for those who are less resilient, and the long-term consequences of these behavioral changes will need to be reassessed. On the other hand, parenthood was significantly associated with higher levels of resilience 5 , pointing to the crucial contribution of a healthy work-family balance to the healthcare providers’ psychological well-being during this pandemic 32 . Indeed, being a parent could lead to overall well-being, a more positive emotional experience and meaning from one moment to the next 33 .…”
Section: Discussionmentioning
confidence: 97%
“…Stress contributes to unhealthy behaviors 30 , 31 , in particular for those who are less resilient, and the long-term consequences of these behavioral changes will need to be reassessed. On the other hand, parenthood was significantly associated with higher levels of resilience 5 , pointing to the crucial contribution of a healthy work-family balance to the healthcare providers’ psychological well-being during this pandemic 32 . Indeed, being a parent could lead to overall well-being, a more positive emotional experience and meaning from one moment to the next 33 .…”
Section: Discussionmentioning
confidence: 97%
“…However, unlike their White counterparts, at the start of the pandemic, Black individuals in medicine had personal risks that transcended the general concerns of inadequate personal protective equipment and exposure to infection. 9 For example, many live in communities that have been labeled hotspots for the virus. 9 Black physicians face the risk of contracting COVID-19 within their neighborhoods and daily clinical practice and witness the added perils that bias contributes to patient outcomes at their own institutions.…”
Section: Reflectmentioning
confidence: 99%
“… 9 For example, many live in communities that have been labeled hotspots for the virus. 9 Black physicians face the risk of contracting COVID-19 within their neighborhoods and daily clinical practice and witness the added perils that bias contributes to patient outcomes at their own institutions. That is, Black patients are approximately 2.5 times more likely to be hospitalized and 1.7 times as likely to die from a COVID-19 infection than White patients.…”
Section: Reflectmentioning
confidence: 99%
“…36 It is unclear how the moral injury related to such factors affects suicide rates among Black people in the general population and Black physicians compared to all-cause mortality (which would include complications from COVID-19 infections). 33,37 A U.S. study may have begun to answer this intricate puzzle, since it showed changing suicide trends during the pandemic: opposite effects observed between Black and White residents of Maryland. 38 Among Black residents, suicide mortality appeared to double during the period of progressive closings and reopenings after the first COVID-19 case in Maryland, while suicide mortality appeared to have nearly halved among White residents during the same period.…”
Section: Covid-19 Considerationsmentioning
confidence: 99%